Perilaku Seksual Pranikah Dan Kematangan Beragama Pada Remaja Akhir - Yudhaprawira, Muhammad Rheza, Dra. Zahrotul Uyun, M.Si (2016)
Premarital sexual behavior in adolescents is a behavior that is driven by sexual desire both with the opposite sex or the same sex that is done without going through a formal process of marriage according to the religion and according to the law. One of many factors that influence the occurrence of premarital sexual behavior is the lower religious maturity. Maturity of religion is a belief, a person's consciousness to undergo moral values, religion, which is the basic for life. This study aims to understand, identify and describe the premarital sexual behavior and religious maturity in the late teens. The characteristics of subjects in this study are a) adolescents aged 18 to 21 years, b) Student of 2015 at the private University's faculty in Surakarta, c) are dating and have been dating. In this study used two research methods, open questionnaire and interview. From the results of the open questionnaire screening there were 107 informants. Furthermore, 6 people selected to become informants in the interview method. The results of this study are dating behavior on informants who are dating and have been dating are holding hands, hugging, and kissing. The drive to do premarital sexual behavior are joyful, comfortable, curiosity and their chance to do it. From the religiosity aspect or religious maturity that has been done is implement compulsory worship and Sunnah worship like Dhuha prayer, tahajud prayer, reading the Al-Quran and do almsgiving. In addition informants also often follow religious studies to increase their knowledge about the science of religion.